Phytochemical Investigation of Quranic Fruits and Plants - A Shafaghat (Institue of Medicinal Plants, ACECR, 2010)
Background: Plants and fruits are an essential component of the universe. Human beings have used those as medicine from the very beginning of time. According to holy Quran, the fruits like grape, date, fig, olive and pomegranate are gifts and heavenly fruits of God. Eighteen fruits and plants name have been mentioned in the holy book of Moslem. A phytochemical screening of these fruits and plants belonging to 15 families was carried out. Objective: This study was conducted to phytochemical investigation on fruits and plants that has been mentioned in Holy Quran. Methods: The plant species are: Olea europaea L., Vitis vinifera L., Punica granatum L., Phoenix dactylifera L., Alhagi mannifera Desf., Ficus carica L., Cedrus deodara (Lawb.)G. Don., Tamarix aphylla L., Salvadora persica L., Zingiber officinale Rosc., Musa sapientum L., Brassica nigra (L.) koch., Lens culinaris medicus., Allium sativum L., Allium cepa L., Cucumis sativus L., Cucurbita maxima Duchartre., and Ocimum basilicum L. Fruits, seeds and other material of the plants screened in this investigation were collected and/or purchased from different grocery and fruit shop during the seasonable period, dried in shadow, and then powdered, some fruits used as fresh sample. A qualitative phytochemical analysis was performed for the presence of flavonoids, alkaloids, tannins and saponins. Results: The results obtained of the investigated plants showed that the all 18 samples were found to be flavonoids bearing, 9 showed the presence of alkaloids, 10 tannins and 10 saponins. Conclusion: The methanolic extract of Phoenix dactylifera L., Olea europaea L., Ficus carica L., Cedrus deodara (Lawb.) G.Don., Tamarix aphylla L., Salvadora persica L., Zingiber officinale Rosc., Brassica nigra (L.) Koch. Allium sativum L. and Allium cepa L. mentioned in holy Quran are rich sources of flavonoids that appear to have protective effects for human health. The Quranic fruits and plants which are medicinal species used for various ailments.